ANALISIS EFEKTIVITAS DAN EFISIENSI PENERIMAAN PAJAK DAERAH PROVINSI SULAWESI UTARA PERIODE 2013-2017 - Talondong, Susanti; Morasa, Jenny; Tangkuman, Steven J. (Universitas Sam Ratulangi, 2018)
Regional Tax is one of the biggest revenues of the regional government. To optimize local tax revenue, it is necessary to see the effectiveness and efficiency of the regional tax. The objectives of this study are (1) to determine the level of effectiveness of local tax revenues in North Sulawesi Province in 2013-2017 (2) to determine the level of efficiency of local tax revenues in North Sulawesi Province in 2013-2017. This research was carried out at the Office of the North Sulawesi Province Tax and Retribution Management Agency (BP2RD). The analytical method used in this research is quantitative descriptive analysis. The research results obtained are that local tax revenue from 2013-2017 has the highest variation in revenues in 2017 at 107.65% and the lowest in 2015 amounted to 91.66%. The level of effectiveness and efficiency of local tax revenues in North Sulawesi Province from 2013-2017 is very effective and efficient.Keywords: Local Tax, Effectiveness, Efficient